Stable 'arrested' non-aqueous edible foams based on food emulsifiers. Issue 6 (15th March 2017) - Patel, A. R.
Abstract : Stable oil foams with structured air–oil interfaces and high overrun ( φ air ≫ 0.5) were fabricated using edible emulsifiers (sucrose esters and lecithin). Abstract : Stable oil foams with structured air–oil interfaces and high overrun ( φ air ≫ 0.5) were fabricated using edible emulsifiers (sucrose esters and lecithin). Advanced microscopy was used to understand the microstructure of these 'arrested' non-aqueous foams which displayed interesting rheological behaviour (yielding and thixotropy). Such complex colloids stabilized by edible ingredients could find important industrial applications in the development of novel textured food products.